Mastery of Information and Communication Competences among Croatian University Students in Social Sciences - Božić, Jasmina (Array, 2008)
The paper analyses the research results of self-assessment of mastery over information and communication competences among students of pre-graduate studies in social sciences at three faculties of the University of Zagreb. The research instruments were applied to purposive sample of students, results are analysed by appropriate statistical tests and interpreted in the context of endeavours in the sphere of higher education to contribute to development of the Croatian society towards knowledge society, particularly in the context of gender, cooperation and competitiveness. Results reveal no significant differences between female and male students in self-assessment of mastery of ICT skills, weak positive correlations of both cooperation and competitiveness with the ICT skills mastery, and prevalence of individual-based forms of exercising information literacy over those that require infrastructural institutional support.